2014
DOI: 10.1016/j.anndiagpath.2014.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Antral atrophy, intestinal metaplasia, and preneoplastic markers in Mexican children with Helicobacter pylori–positive and Helicobacter pylori–negative gastritis

Abstract: Chronic inflammation and infection are major risk factors for gastric carcinogenesis in adults. As chronic gastritis is common in Mexican children, diagnosis of Helicobacter pylori and other causes of gastritis are critical for the identification of children who would benefit from closer surveillance. Antral biopsies from 82 Mexican children (mean age 8.3±4.8y) with chronic gastritis (36 H. pylori +, 46 H. pylori -) were examined for gastritis activity, atrophy, intestinal metaplasia, and immunohistochemical e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 42 publications
0
22
0
2
Order By: Relevance
“…Although there are studies reported the relationship of intestinal metaplasia and H.pylori infection, some of the authors reported no relations [18][19][20][21]. As a result of the analysis of the histopathological analysis; H.pylori infection and intestinal metaplasia Similarly, there is not an accepted evidence of dominancy of any gender in literature there was not a gender dominancy of H.pylori infection.…”
Section: Discussionmentioning
confidence: 69%
“…Although there are studies reported the relationship of intestinal metaplasia and H.pylori infection, some of the authors reported no relations [18][19][20][21]. As a result of the analysis of the histopathological analysis; H.pylori infection and intestinal metaplasia Similarly, there is not an accepted evidence of dominancy of any gender in literature there was not a gender dominancy of H.pylori infection.…”
Section: Discussionmentioning
confidence: 69%
“…H. pylori induction of p53 expression has been described in chronic gastritis and preneoplasic lesions (such as intestinal, metaplasia and dysplasia in adults), especially those associated with CagA-positive strains (Teh et al, 2002;Li et al, 2016). Pediatric studies assessed in this review showed contradictory results, with p53 overexpressed in gastric tissue of H. pylori infected children, and directly correlated with gastritis, the magnitude of inflammatory cell infiltration and H. pylori tissue density in two studies (Ozturk et al, 2005;Saf et al, 2015); while on the other hand two other studies showed similar expression levels in infected and non-infected children (Nardone et al, 2001;Villarreal-Calderon et al, 2014).…”
Section: Transcription Factorsmentioning
confidence: 75%
“…H. pylori promotes the Wnt/β-catenin pathway through several mechanisms: by upregulating Wnt/β-catenin activators, c-Met and EGFR, by downregulating the Wnt/β-catenin suppressors, TFF1 and RUNX3, and also by recruiting tumorassociated macrophages (Song et al, 2015). Villarreal -Calderón et al, describe high membranous expression of β-catenin in gastric biopsies of H. pylori infected children as compared to non-infected controls (Villarreal-Calderon et al, 2014).…”
Section: Transcription Factorsmentioning
confidence: 99%
“…The cross‐sectional studies on H. pylori infection in symptomatic children as detected by histology are summarized in Figure [references: ] . H. pylori prevalence estimates vary greatly (3%‐76%) with an overall random‐effects regression model estimate of 39% (95% CI: 35%‐43%).…”
Section: Resultsmentioning
confidence: 99%
“…Among children with gastrointestinal symptoms, rates varied from 7% to 76%, with a cluster of studies, 16/43 (37%), reporting prevalence estimates of 30%‐40%. Three studies in children with gastritis or duodenitis reported a 44% positivity rate in Mexico, 46% in Russia and 20% in China . One study in Europe looked at infection rates in children with gastric or duodenal ulcers, in children <6 years old 13% were infected, in 6‐11‐year‐olds 35% and in 12‐18‐year‐olds 38% were infected .…”
Section: Resultsmentioning
confidence: 99%